A régiók jelene és jövője Magyarország példáján - Pál, Ágnes; Nagy, Gábor (Közép-Európai Közlemények, 2009)
Research into various regions and the differences between them has always been a standard topic in the academic world. Various disciplines are targeted at describing the core problems. The aim of this paper is to repeatedly ask a well-known question, i.e. whether or not in Hungary the regional differences have lessened in the recent years, and also, whether or not they are possible to eliminate. Can we expect a significant change in this respect in the future? The paper is not aimed at finding in ultimate answer to these questions, instead, it attempts to give an overview of the possible answers.